Accruals, Intellectual Capital, Change In Equity, Change In Short-Term Debt, dan Change In Long-Term Debt Stock Return Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Supriyanto, Supriyanto; Selly, Selly (Faculty of Economics, Universitas Internasional Batam, 2017)
The purpose of this research is to analyze the effect of Accruals, Intellectual Capital, Change In Equity, Change In Short-term Debt, and Change In Long-term Debt of stock return. The dependent variable in this research is Stock Return. The independent variables are Accruals, Intellectual Capital, Change In Equity, Change In Short-term Debt, and Change In Long-term Debt. This research also use the control variable is Return On Equity, Revenue Growth, Market To Book Value, Firm Size, and Book To Market Ratio. The sample is companies listed on Indonesia Stock Exchange during the period 2009 to 2013. The sample of research were selected using the purposive sampling method and 250 companies used in this research. The result of this research show accruals, firm size, and control variable market to book value is significant positive, intellectual capital, change in equity, change in short-term debt, change in long-term debt, and control variable book to market ratio, return on equity, and revenue growth is insignificant effect on stock return.